Heart Failure in a Young Adult with a Fine-Lubinsky Syndrome: An Unknown Comorbidity - Blake Purtle; Jason Wagner; Andrew Zarker; Vishal Patel; David Aguilar (Case Reports in Cardiology)
The Fine-Lubinsky syndrome (FLS) is a rare congenital disorder. Heart failure has not been described in young adults with this condition. Here, we report the first case of heart failure in a young adult patient with FLS. This finding highlights the need for further investigation into cardiac complications in this illness.